Information Asymmetry in Financial Markets: Challenges and Threats - Ivanitsky, Viktor Pavlovich; Tatyannikov, Vasiliy Arkadevich (Economy of Regions, 2018)
The article analyzes the contradictions that have developed on the modern stock market. Markets are becoming more volatile, which creates conditions for manipulating prices on individual financial instruments. The institutional regulation does not solve these problems and, ultimately, is limited to an ineffective control over the markets by regulators and the search for new options for economic imbalances by economic agents. We introduce the terminology and justify the notion of «dominant economic agent». The emergence of dominant economic agents is viewed through the instability of the global financial system, through the access of this category of market participants to unique information technologies, when the opportunities to take advantage of information asymmetry give even greater volatility (variability), primarily, to the financial market and its instruments. Increased volatility attracts new economic agents to the financial market. The role of the dominant economic agents is only increasing. Such an unstable equilibrium develops on the market, when any competitive advantage from a local one can turn into a key one. We investigated the mutual influence and interpenetration of the postulates of the theory of effective financial (stock) markets and the theory of asymmetric information. The hypothesis of the research is based on expert assessments and the practice of financial instruments circulation. Furthermore, the hypothesis confirms that the levels of stock markets efficiency associated with the receipt of new information are erased due to the subjective behaviour of the dominant economic agents. It is not possible to prove that the actions of the dominant economic agents, through the high volatility of financial instruments and individual market segments, lead to the manipulation of the market within the framework of the existing regulatory standards. However, it is undeniable that an excessive volatility of certain financial assets creates problems for accelerating market transformations and institutional changes in the Russian economy. Under current conditions, we recommend solely passive asset management strategies, where fixed-income instruments are basic, and the investor does not need to track the dynamics of changes in their prices, and the effect of information asymmetry is minimized. We have proposed and justified a modern interpretation of investment risk. This interpretation suggests taking into account not only the market dominant, but also the behavioural component. This component is based on the psychology of the agents behaviour on the market, and also on the asymmetry of information on the financial markets that dominate economic agents. The results of the study have theoretical and practical significance and can be used both in the development and implementation of measures in the field of financial market regulation, as well as in analyzing the low activity of the population in the investment process.